The Arctic Population: Dynamics and Centers of the Settlement System - Andrey V. SMIRNOV (Arctic and North, 2020)
The article presents an estimate of the Arctic population in 1900–2019 by country and macro-region, obtained using official statistics of eight Arctic States. Analysis of spatial and temporal data revealed the main patterns of the Arctic population formation. Calculations show the world’s Arctic population in-creased from 1.3 million in 1900 to 6.1 million in 1989, and then declined to 5.4 million in 2019. The share of Russia varied from 22% to 58%. The data show that interregional migration in the Russian Arctic had a decisive influence on the demographic dynamics of the Arctic in general. The main reasons for the decline in the Arctic population in different periods were the completion of cycles of natural resource development and lower quality of life in comparison with the central regions. To smooth out differences in national statistical accounting systems, the article examines the dynamics of the population in 17 major centers of settlement in the Arctic, where more than two-thirds of the population lives. Calculations show that urbanization and population concentration in several of the most attractive areas of the Arctic continue. Administrative and educational centers, which are points of attraction for residents of other Arctic territories, get an advantage. The results of the study allow us to predict the further evolution of the Arctic settlement system. They can be used in the development of strategies and programs for the spatial development of the North and the Arctic.